Population Behavior and Practices during the First Wave of COVID-19 Pandemic in Low Resource-Conditions of South Kivu, East of Democratic Republic of Congo - Rodrigue Balthazar Basengere Ayagirwe; Bwihangane Birindwa; Chasinga Baharanyi; Baenyi Patrick; Theophile Kashosi; Basimane Bisimwa Parvine; Tonui Ronald; Mugumaarhahama Yannick; Mutwedu Valence; Bwami Baharanyi Joyeux; Wasso Shukuru Dieudonné; Bisimwa Ntagereka Patrick; Mukwege Denis (Journal of Epidemiology and Public Health, 2022)
Background: In DR Congo, South Kivu is among the cities most affected by COVID-19 with its dense population and common mass movement. This study aimed to investigate the population behavior and practices during the spread period of Corona in South Kivu, East of the Democratic Republic of Congo. Subjects dan Method: A cross-sectional analytical study was undertaken in South Kivu province and included 800 hundred individuals. The survey questionnaire was designed and comprised information on independent variables including socio-demographic and socioeconomic parameters, travel history of individuals, and person's history of COVID-19 comorbidity factors. These data were used to explain the dependent variable which was the population behavior and practices which was linked to the COVID-19 positivity or negativity. A rapid test of the COVID-19 antigen for people suspected of having cough and fever followed by RT-PCR tests was conducted. Statistical analyses were performed under R, version 3.5.1. Results: Results indicate three categories of people depending on their behavior and practices during the COVID-19. These include the negative group, those who contracted the disease and knew their serological status, and those who did not know their serological status. The behavior of these categories varied with age, education level, income, and their geographical location. Variable behaviors have been adopted, including lack of action, prayer, self-medication, lifestyle change, and change in feeding. Efforts to control the spread of the disease entailed two most commonly used barriers: wearing a mask (95%) and frequent hand washing (94%). In the COVID-19 infected category, type 1 individuals developed the most characteristic symptoms of COVID-19, mainly cough, asthenia, fever, and headache. Types 2 and 3 individuals were less likely to engage in any of the behaviors associated with COVID-19 because they have fewer comorbidities and have developed fewer of the symptoms characteristic of COVID-19. Conclusion: Education level and socioeconomic conditions are among the factors to be considered in pandemic control strategies. Keywords: Typology, SARS, comorbidity, population believe. Correspondence: Ayagirwe Rodrigue Basengere. Bioscience unit, Université Evangélique en Afrique. Bukavu, PO Box 3323, Democratic Republic of Congo. Email: rayagirwe@gmail.com. Mobile: +243979318796.